2014
DOI: 10.3747/pdi.2012.00290
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Ultrafiltration in Refractory Heart Failure: A Cohort Study

Abstract: ♦ Introduction: Acutely decompensated heart failure (HF) in patients with diuretic resistance is often treated with extracorporeal ultrafiltration. Peritoneal ultrafiltration (PUF) has been proposed for the long-term management of severe HF after resolution of the acute episode. The aim of the present study was to evaluate the use of PUF in the treatment of chronic refractory HF in patients without endstage renal disease. ♦ Methods: This multicenter (10 nephrology departments throughout Italy) retrospective ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
67
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 23 publications
(34 reference statements)
14
67
2
5
Order By: Relevance
“…Many, if not most, studies have addressed this issue, usually by retrospective comparison to previous admission days, and shown marked reduction in presentations and hospital bed days after institution of therapy (27)(28)(29). A crude figure for the reduction in admissions has been estimated to be ~83% (30) which, if proven in RCTs would almost certainly add substantial economic weight to the proponents of this therapy.…”
Section: Hospitalizationsmentioning
confidence: 99%
“…Many, if not most, studies have addressed this issue, usually by retrospective comparison to previous admission days, and shown marked reduction in presentations and hospital bed days after institution of therapy (27)(28)(29). A crude figure for the reduction in admissions has been estimated to be ~83% (30) which, if proven in RCTs would almost certainly add substantial economic weight to the proponents of this therapy.…”
Section: Hospitalizationsmentioning
confidence: 99%
“…PUF was found to decrease the rate of hospitalization because of acute decomposed HF in several studies (56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Peritoneal Dialysis In Heart Failurementioning
confidence: 98%
“…In many of the other studies that examined the effect of PUF on GFR, PUF was found to be ineffective on GFR (42,56,68,79). In a meta-analysis including six studies with a total of 282 patients without indications of renal replacement therapy, there was no significant difference in GFR before and after PUF (80).…”
Section: How Does Peritoneal Dialysis Affect Glomerular Filtration Rate?mentioning
confidence: 99%
See 1 more Smart Citation
“…Bertoli ve ark. da böbrek fonksiyonu normal ve diüretik dirençli 48 kalp yetmezliği hastasında benzer faydalar elde etmişlerdir (47). Periton diyalizi ile ultrafiltrasyon günlük 1 değişimden ihtiyaca göre artırılmak suretiyle artırımlı peritoneal ultrafiltrasyon şeklinde uygulanabilir.…”
Section: Kalp Yetmezliğinde Peritoneal Ultrafiltrasyonunclassified